2007
DOI: 10.1136/bjsm.2007.035436
|View full text |Cite
|
Sign up to set email alerts
|

Physical performance changes after unsupervised training during the autumn/spring semester break in competitive tennis players

Abstract: Background: All competitive tennis players take time away from coaches throughout the year; however, little information is available as to the short-term physiological effect of these breaks. Objective: The purpose of this investigation was to evaluate the impact of a 5 week off-campus structured, yet unsupervised, break from regular training in top collegiate tennis players. Methods: A nationally ranked collegiate NCAA Division I male tennis team (n = 8) performed a test battery in December and again in Janua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
61
1
5

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(70 citation statements)
references
References 27 publications
(20 reference statements)
3
61
1
5
Order By: Relevance
“…Consequently, the players' jumping performance was probably poorer due to training reductions during the summer and then, after one season of regular training, the players in both groups experienced normal adaptation to sport. Previous studies have shown that the physical performance, such as jumping performance and throwing velocity, were enhanced during one season of ordinary training or preparation for competition in sports 21,30 and that interruptions in normal training can result in physical capacity reductions 31 . Since jumping is one of the most important tasks in volleyball, it is likely that this ability will improve during one season of volleyball training.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, the players' jumping performance was probably poorer due to training reductions during the summer and then, after one season of regular training, the players in both groups experienced normal adaptation to sport. Previous studies have shown that the physical performance, such as jumping performance and throwing velocity, were enhanced during one season of ordinary training or preparation for competition in sports 21,30 and that interruptions in normal training can result in physical capacity reductions 31 . Since jumping is one of the most important tasks in volleyball, it is likely that this ability will improve during one season of volleyball training.…”
Section: Discussionmentioning
confidence: 99%
“…Based on our finding, it appears there is specific need to address the challenges of obtaining HRV recordings throughout the competitive season. Emphasizing the importance of maintaining compliance during all periods of the season by coaches may help mitigate this problem (21).…”
Section: Discussionmentioning
confidence: 99%
“…This performance-based test requires little equipment or experience to perform and is generally hypothesized to be a refl ection of anaerobic capacity [3,9,11,21] . Some authors have suggested that the WAnT may not be the most appropriate test for assessing anaerobic power in athletes [22,32] . A common concern in these studies was the applicability of a cycle ergometer test for assessing anaerobic power in athletes who primarily perform sprinting activities.…”
Section: Introduction ▼mentioning
confidence: 99%